Sustaining Thai SMEs through perceived benefits and happiness - Winit W. (2017)
© 2017, © Emerald Publishing Limited. Purpose: This paper aims to examine the relationship between stakeholders’ perceived benefits and happiness of small and medium-sized enterprises (SMEs) that follow Thai’s corporate sustainability practices, called sufficiency economy, and their impact on stakeholder–company relationship quality and firm performance outcomes. Design/methodology/approach: Derived from the literature, a structural model, expressing the relationship between stakeholders’ perceived benefits and happiness of SMEs and their impact on stakeholder–company relationship quality and firm performance outcomes, was developed. A questionnaire survey was conducted with 636 stakeholders from sufficiency economy SMEs in Thailand. Structural equation modeling was used to test the model. Findings: Results indicate that utilitarian benefits, and hedonic and eudaimonic happiness impact enhanced stakeholder–company relationship quality with the firm to varying degrees. Different levels of relationship quality also impact perceived corporate reputation and perceived brand equity differently. Originality/value: This study is among the first that identifies the positive impact of happiness on corporate sustainability performance.